Productivity Research in the Behavioral and Social SciencesProductivity Research in the Behavioral and Social Sciences by BriefArthur P. (Editor). New York: Praeger, 1984, 301 pp., $24.95.Productivity: Problems, Prospects, and Policies, by LevitanSar A. WernekeDiane. Baltimore: Johns Hopkins University Press, 1984, 125pp., $15. - Schmitt, Neal (Academy of Management Review, 1985)
The article reviews the books & "Productivity Research in the Behavioral and Social Sciences,& " by Arthur P. Brief and & "Productivity: Problems, Prospects, and Policies,& " by Sar A. Levitan and Diane Werneke.